Underrepresentation and distortion of identity in mass media during labour dispute: The case of the Bershka workers’ - Barreiro González, Mª Soliña; Fernàndez i Aragonès, Aina (Sociología del Trabajo, 2019)
News in mass media is still a battlefield during labour conflicts, even if social media has an increasing role because media are a pressure strategy and conflict socialization space. Workers usually fight against silence and distortion. This paper analyzes media coverage on the larger strike developed against Inditex, that has been organized by Pontevedra Bershka women workers in 2017.These workers had to break media silence –a complicated situations due to Inditex influence– and they had to overcome prejudices based on their youth and sex. In order to achieve their objectives, they applied traditional trade union strategies (as demonstrations and picket lines) and new strategies to reach the media setting (social media, comment on digital news, video pamphlets…). This paper combines different methodologies: it analyzes the conflict storytelling built by media and the counter-storytelling developed by the workers through news content analysis (Framing theory), through the analyses of the materials developed by the workers and through the content study of in-depth interviews conducted by the researchers to workers and journalists.